دور المحيط الاجتماعي الثقافي في تطوير النشاط البدني الرياضي النسوي دراسة ميدانية لبعض تلميذات المرحلة الثانويات لمقاطعتي المراهنة والتاورة بولاية سوق اهراس (19_16 سنة) - إيمان غالمي (sports creativity, 2025)
هدفت هذه الدراسة إلى محاولة الكشف عن تطور الممارسة الرياضية للفتيات المراهقات المتمدرسات في المرحلة الثانوية ( 16- 19 سنة) وفقا للمحيط الاجتماعي والثقافي وهذا انطلاقا من استقصاء بعض ثانويات ولاية سوق اهراس ، وقد استخدمت الباحثة المنهج الوصفي حيث اخذنا من مجموع البحث الذي يبلغ179تلميذة عينة من التلميذات المعفيات التي قدرت ب 30تلميذة هذا من خلال الاجابة على اسئلة استمارة الاستبيان كلهم ينتمون الي بعض ثانويات مقاطعتي المراهنة وتاورة بولاية سوق اهراس، و اعتمد الباحثة في تحليلها على اربعة فرضيات من خلالها حاولت الكشف عن دور المحيط الاجتماعي الثقافي في تطوير الممارسة الرياضية بالنسبة للمراهقات المتمدرسات لبعض ثانويات مقاطعتي تاورة والمراهنة بولاية سوق اهراس، وبعد جمع البيانات والمعلومات وتحويلها من معلومات كيفية الي كمية توصلت الباحة في الأخير إلى النتائج التالية: ان السبب الرئيسي لتطوير رياضة الفتيات المراهقات في الوسط الثانوي تعود الى المحيط الاجتماعي والمحيط الثقافي السائد في المنطقة ابتداء من الاسرة والمجتمع وصولا الي المدرسة او المؤسسة التربوية، التي في وقت ما كانت تتنافى وممارسة الفتات للرياضة في المنطقة . This study aimed to detect the development of sports practice for adolescent girls in the secondary level , aged between (16 to 19)years old in accordance with their social and cultural surroundings and this is on the light of a survey made in some of the Lycees in the wilaya of Souk Ahras , where the researcher used a descriptive approach . The survey was submitted to a total of 179 female informants as a sample of exempted pupils from sport . According to 30 among the latter answers to the questionnaire addressed to the learners mainly in Merahna and Taoura , two localities of the wilaya, the result according the analysis of the researcher was based on four hypotheses leading to the role of the socio- cultural environement in the development of the sports practice concerning the adolescent schollars in the lycees of Merahna and Taoura in the wilaya of Souk Ahras , after the collection of all charts and information ,the researcher found out that : the main cause in female secondry adolescent learners’ sport’s practice is due to the social and cultural environement predominant in their dwelling locality and this is starting from the family and society milieu to the school or the educational institution one that was against the practice of sport of the female within the region.